Predictive control in process engineering : from the basics to the applications - Haber, Robert, 1948- (Wiley-VCH ; John Wiley [distributor], 2011)
Describing the principles and applications of single-input, single-output and multivariable predictive control in a simple and lively manner, this practical book also considers such issues as the handling of on-off control, nonlinearities and decoupling problems. It gives guidelines and methods for reducing the computational demand for real-time applications. With its many numerical examples and several case studies (incl. injection molding machine and waste water treatment) and industrial applications (stripping column, distillation column, furnace) this is invaluable reading for students and engineers who aim to understand and apply predictive control in a wide variety of process engineering application areas.